Adherence of the Turkish Population's Dietary Pattern to the EAT-Lancet Planetary Health Diet Recommendations - Merve Esra Çıtar Dazıroğlu (Journal of Gazi University Health Sciences Institute, 2026)
The EAT-Lancet Planetary Health Diet (PHD) has emerged as a global dietary model that supports both human health and environmental sustainability within sustainable food systems. However, the evidence regarding adherence of the Turkish population to the PHD remains limited. This study evaluated adherence to the EAT-Lancet PHD among the Turkish population using the data from the Türkiye Nutrition and Health Survey (TNHS)-2017. EAT-Lancet reference values were adjusted according to the mean daily energy intake of each age and sex group. Mean daily food group intakes were compared with these adjusted values to calculate adherence percentages. Adherence to vegetables and fruits ranged from 82.4–148.3% and 70.2–164.1%, respectively, whereas legumes (24.8–30.9%) and nuts (13.0–28.1%) remained well below the recommended levels in all groups. Fish intake was also below the recommended level in all groups (27.1–64.5%), with particularly lower adherence among individuals aged 15–18 years. Egg (189.5–285.7%) and red meat (262.3–371.4%) consumption exceeded not only the reference values but also the recommended maximum intake levels in all groups. Adherence to poultry and milk and dairy products ranged from 65.1–140.2% and 88.0–119.8%, respectively, with lower poultry adherence observed among individuals aged ≥65 years. Overall, the dietary pattern of the Turkish population demonstrated limited adherence to the EAT-Lancet PHD, characterized by excessive red meat and egg consumption and insufficient legume, nut, and fish consumption. This study provides the first nationally representative evidence on adherence to the EAT-Lancet PHD in Türkiye.